Skeletal muscle index combined with IgM predicts prognosis in gastric cancer patients who underwent surgery - Xu, Yunxin; Xing, Yue; Du, Zhongze; Zhao, Ruihu; Deng, Guiming; Song, Haibin; Xue, Yingwei; Song, Hongjiang (Frontiers in Immunology, 2025)
BackgroundThe purpose of this study is to investigate the combination of skeletal muscle index (SMI) and immunoglobulin M (IgM) to form the SMI-IgM score to predict the prognosis of patients who underwent surgery for gastric cancer.Patients and methodsIn this study, 190 patients operated for gastric cancer from July 2016 to December 2017 were collected. According to the optimal critical values of skeletal muscle index and immunoglobulin M, all patients were divided into three groups. We used Kaplan-Meier survival curves and log-rank test to assess the differences in progression-free survival time (PFS) and overall survival time (OS) between the 3 groups of patients. Independent predictors were identified using Cox regression, and nomogram plots were produced to predict confounded 1-, 3-, and 5-year survival rates based on independent predictors.ResultsThere were 68 patients (35.8%) in the SMI-IgM 1 group, 85 patients (44.7%) in the SMI-IgM 2 group, and 37 patients (19.5%) in the SMI-IgM 3 group. Patients in the SMI-IgM 1 group had worse PFS (HR = 0.345, 95% CI: 0.226-0.525, p < 0.001) and OS (HR = 0.345, 95% CI: 0.227-0.525, p < 0.001). The multifactorial analysis showed that SMI-IgM score was an independent predictor of PFS and OS in patients. The calibration curves show better predictive efficacy of the column charts in years 3 and 5.ConclusionThe SMI-IgM score could well respond to the nutritional and immune status of the body, and could be used as a new predictor for patients undergoing surgery for gastric cancer.